Adiponectin as Novel Regulator of Cell Proliferation in Human Glioblastoma. Issue 10 (October 2014) - Porcile, Carola; Di Zazzo, Erika; Monaco, Maria Ludovica; D'Angelo, Giorgia; Passarella, Daniela; Russo, Claudio; Di Costanzo, Alfonso; Pattarozzi, Alessandra; Gatti, Monica; Bajetto, Adriana; Zona, Gianluigi; Barbieri, Federica; et al.
<x xml:space="preserve">Abstract</x> Adiponectin (Acrp30) is an adipocyte‐secreted hormone with pleiotropic metabolic effects, whose reduced levels were related to development and progression of several malignancies. We looked at the presence of Acrp30 receptors in human glioblastomas (GBM), hypothesizing a role for Acrp30 also in this untreatable cancer. Here we demonstrate that human GBM express Acrp30 receptors (AdipoR1 and AdipoR2), which are often co‐expressed in GBM samples (70% of the analyzed tumors). To investigate the effects of Acrp30 on GBM growth, we used human GBM cell lines U87‐MG and U251, expressing both AdipoR1 and AdipoR2 receptors. In these cells, Acrp30 treatment inhibits DNA synthesis and cell proliferation rate, inducing arrest in G1 phase of the cell cycle. These effects were correlated to a sustained activation of ERK1/2 and Akt kinases, upon Acrp30 treatment. Our results suggest that Acrp30 may represent a novel endogenous negative regulator of GBM cell proliferation, to be evaluated for the possible development of novel pharmacological approaches. J. Cell. Physiol. 229: 1444–1454, 2014. © 2014 Wiley Periodicals, Inc.